PENGARUH GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Survei Pada Konsumen The Body Shop di Indonesia dan di Malaysia) - Luh Made Pradnyani Rahayu; Yusri Abdillah; M. Kholid Mawardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
This research aims to examine the influence of green marketing straegy towards purchasing decision in either silmultaneously and partially as well as to identify any differences in the effect of green marketig towards purchasing decision of consumers in Indonesia and Malaysia. The type of this research is explanatory research with quantitative approach. Variables used in this research are Environmental Awarenes (X1), Green Product Features (X2), Green Product Price, Green Product Promotion (X4) and Purchase Decision. The research population are the people who live in Jakarta-Indonesia and Kuala Lumpur-Malaysia who are consumers of green products The Body Shop. Total sample in this study is as much as 113 respondents. Methods of data collection using a questionnaire distributed through google forms. The data analysis used are multiple linear regression analysis and comparative analysis. The analysis showed that there is a significant influence together and partially between variables Environmental Awareness (X1), Green Product Features (X2), Green Product Price (X3), Green Product Promotion (X4) towards Purchase Decision (Y). The results of the comparative analysis showed no significant differences between the effects of environemtal awareness, green product features, green products and green product promotion price on purchase decisions among consumers in Indonesia and in Malaysia. Key Word: environemtal awareness, green product features, green product price, green product promotion, purchase decision. ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menjelaskan dampak dari strategi green marketing terhadap keputusan pembelian baik secara bersama-sama maupun parsial dan juga untuk mengetahui dan menjelaskan perbedaan pengaruh green marketing terhadap keputusan pembelian antara konsumen di Indonesia dan di Malaysia. Jenis penelitian ini adalah penelitian eksplanatori dengan pendekatan kuantitatif. Variabel yang digunakan dalam penelitian ini adalah Environmental Awareness (X1), Green Product Features (X2), Green Product Price (X3), Green Product Promotion (X4), dan Keputusan Pembelian (Y). Populasi penelitian ini adalah masyarakat yang berdomisili di Jakarta-Indonesia dan Kuala Lumpur-Malaysia yang merupakan konsumen produk hijau The Body Shop. Total sampel dalam penelitian ini adalah sebanyak 113 orang responden. Metode pengumpulan data menggunakan kuesioner atau angket yang disebarkan melalui google forms. Analisis data yang digunakan adalah analisis regresi linier berganda dan analisis komparatif. Hasil analisis menunjukkan bahwa terdapat pengaruh yang signifikan secara bersama-sama dan secara parsial antara variabel Environmental Awareness (X1), Green Product Features (X2), Green Product Price (X3), Green Product Promotion (X4) terhadap Keputusan Pembelian (Y). Hasil analisis uji beda independent t-test menujukkan tidak terdapat perbedaan yang signifikan antara pengaruh environemtal awareness, green product features, green product price dan green product promotion terhadap keputusan pembelian antara konsumen di Indonesia dan di Malaysia. Kata kunci: environemtal awareness, green product features, green product price, green product promotion, keputusan pembelian.